2019
DOI: 10.1136/bmjopen-2019-029590
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and influencing factors of physical activity and sedentary behaviour in the rural population in China: the Henan Rural Cohort Study

Abstract: ObjectivesTo estimate the prevalence and influencing factors of physical activity (PA) and sedentary behaviour (SB) in rural areas of China.DesignCross-sectional study.SettingA multistage, stratified cluster sampling method was used to obtain samples in the general population of Henan province in China.Participants38 515 participants aged 18–79 years were enrolled from the Henan Rural Cohort Study for the cross-sectional study.Main outcome measuresThe International Physical Activity Questionnaire was used to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…The total value of MET was obtained by adding value of these three categories. Finally, based on the standard scoring criteria of IPAQ, three levels of PA were determined: the light (physically inactive) activity category was for individuals who met neither moderate activity nor vigorous activity criteria, moderate activity should meet either of the following four criteria: (1) [16]. The individual total ST every day in the past week was estimated by using the question "About how many hours in each 24-h day do you usually spend on sitting?…”
Section: De Nitions Of Exposurementioning
confidence: 99%
“…The total value of MET was obtained by adding value of these three categories. Finally, based on the standard scoring criteria of IPAQ, three levels of PA were determined: the light (physically inactive) activity category was for individuals who met neither moderate activity nor vigorous activity criteria, moderate activity should meet either of the following four criteria: (1) [16]. The individual total ST every day in the past week was estimated by using the question "About how many hours in each 24-h day do you usually spend on sitting?…”
Section: De Nitions Of Exposurementioning
confidence: 99%
“…PA and ST levels were assessed by using the International Physical Activity Questionnaire (IPAQ) [20]. As the details have been described previously [16,19], PA-metabolic equivalent (MET) was calculated by using MET coe cient of activity × duration (hour per time) × frequency (times per week) [19]. Therefore, according to the categories of PA, each category of vigorous activity, moderate activity and walking was calculated with the corresponding MET values of 8, 4, and 3.3 respectively.…”
Section: De Nitions Of Exposurementioning
confidence: 99%
“…The total value of MET was obtained by adding value of these three categories. Finally, based on the standard scoring criteria of IPAQ, three levels of PA were determined: light (physically inactive), moderate and vigorous [16]. The individual total ST every day in the past week was estimated by using the question "About how many hours in each 24-h day do you usually spend on sitting?…”
Section: De Nitions Of Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…Chinese adolescents were also found to be physically inactive, with only 10.3% performing moderate-to-vigorous PA for more than 60 min per day on five days a week, as recommended [6]. Furthermore, it has been shown that PA participation of Chinese adolescents varies by gender, with males more likely to be physically active than females [7][8][9]; in this case, gender is usually considered in the research to investigate correlates of PA.…”
Section: Introductionmentioning
confidence: 99%